Forestry in the Middle East and North Africa : An Implementation Review - Pswarayi-Riddihough, Idah (Washington, DC: World Bank, 2013)
In the Middle East and North Africa Region, forest resources are generally limited, as is their contribution to GDP, and it is for this reason their importance is often overlooked. However, forestry's contribution to natural resource and environmental management, is significant, which should not be underestimated. The report, implemented as an input to the development of a Bank Forestry Strategy in guiding its work in the sector, reviews the Bank-assisted forestry projects in the region over the last ten years, defines the regional forests, and describes its current status, and related policy and economic issues, including the need of civil society, and private sector involvement in forestry related issues. It is highlighted that ultimately, the decisions taken on the directions to be followed by the Bank, would be based on sound knowledge of the overall regional aspects, proposing Economic and Sector Work for the future. The report outlines appropriate policy formulation and technical solutions, but emphasizes that local communities must be directly involved in the planning, implementation, and monitoring of forestry development activities. This approach implies that public administrations, responsible for forestry development, become fully decentralized, and capable of strengthening local capacity.